Association of milk production traits with genetic variants in exon 5 and intron 3 of bovine growth hormone (bGH) gene in Sahiwal cattle - SACHAN, SHWETA; GUPTA, I D; VERMA, ARCHANA; KUMAR, ANSHUMAN; VINEETH, M R (The Indian Journal of Animal Sciences, 2021)
The main objective of this study was to determine the association of production traits with genetic variants in exon 5 and intron 3 of bovine growth hormone (bGH) gene in Sahiwal cattle. The analyses were based on the detection of single nucleotide polymorphisms (SNPs) in GH-AluI (exon 5) and GH-MspI (intron 3) using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assay. The frequency of AluI (L/V) and MspI (T/C) alleles were 86.20/13.70 and 89.80/9.50, respectively. The distribution of the frequency of GH genotypes for LL, LV, and VV were 73.4, 25.5, and 1.0 and for TT, TC, and CC genotypes were 80.9, 17.7, and 13.0, respectively. Season of calving had none but period of calving had significant effect on the studied production traits. The phenotypic data was adjusted for non-genetic factors and regression analysis was done. There was detectable significant effect of the GH-AluI and GH-MspI on the analyzed production traits. The cows with LL genotype had significantly higher milk yield traits than the LV genotype. Similarly, the productive performance of the studied cows with TT genotype was also significantly higher than TC and CC genotypes. Results revealed that the Sahiwal cows with LL and TT genotypes of the bGH locus can be considered to be a favourable genotype for production traits, although these findings need to be confirmed by further research before SNPs can be used in a marker assisted selection program by the animal breeder.